2010
DOI: 10.1136/emj.2009.084384
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric procedural sedation based on nitrous oxide and ketamine: sedation registry data from Australia

Abstract: In variation to reported practice elsewhere, almost all procedures in this Australian series were undertaken using nitrous oxide and ketamine. The serious adverse events rate was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 33 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…There have been many studies illustrating the safe use of ketamine and N 2 O for procedural sedation by ED physicians and intensivists. [3][4][5][6][7] This is the fi rst study demonstrating the safe and effective use of ketamine and N 2 O by PH. It is important to note that a comprehensive sedation training program with anesthesia oversight and close collaboration with anesthesiologists is a key element of the PH sedation program at SLCH.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There have been many studies illustrating the safe use of ketamine and N 2 O for procedural sedation by ED physicians and intensivists. [3][4][5][6][7] This is the fi rst study demonstrating the safe and effective use of ketamine and N 2 O by PH. It is important to note that a comprehensive sedation training program with anesthesia oversight and close collaboration with anesthesiologists is a key element of the PH sedation program at SLCH.…”
Section: Discussionmentioning
confidence: 87%
“…2 Several studies have demonstrated the safety of procedural sedation using ketamine and nitrous oxide (N 2 O) by emergency physicians and intensivists. [3][4][5][6][7] Pediatric intensivists and emergency physicians have been the primary nonanesthesiologist sedation providers because they have the greatest experience managing the pediatric airway in patients in the emergency department (ED) and ICU. However, pediatric hospitalists (PH) are increasingly providing sedation for various painful procedures and for radiologic imaging of children across the nation.…”
mentioning
confidence: 99%
“…59 A fixed nitrous oxide/ oxygen mixture can provide safe and effective analgesia for paediatric medical procedures. [60][61][62][63] Additionally, the equipment needed for its administration is relatively inexpensive, minimal training is required for operators and no additional resuscitation equipment or staff is needed. Thus, there is a need for the introduction of this inhalational analgesic and sedative agent in Chinese scientific literature to conserve medical resources.…”
Section: Open Accessmentioning
confidence: 99%
“…Sedation has both benefits and risks. If managed well, it can be effective and safe, minimising pain and anxiety for patients and parents and providing optimum conditions for the safe completion of procedures . If managed poorly, it carries the risks of unconsciousness, suppression of vital protective airway reflexes and hypoventilation.…”
Section: Introductionmentioning
confidence: 99%
“…If managed well, it can be effective and safe, minimising pain and anxiety for patients and parents and providing optimum conditions for the safe completion of procedures. 3,4 If managed poorly, it carries the risks of unconsciousness, suppression of vital protective airway reflexes and hypoventilation. The keys to safe and successful treatment are case selection, having staff appropriately trained to administer sedation and having strong clinical governance arrangements, especially procedures, to maximise safety and effectiveness.…”
Section: Introductionmentioning
confidence: 99%